Determination Of Porosity Level Of Out Of Autoclave Carbon Epoxy Advanced Composites Using Ultrasonic C-Scan Pulse-Echo Method - Zainal Abidin, Mohd Fadzlee (2017)
Various inspection techniques are available for inspection and quality control in monitoring services of composite structures, which ultrasonic inspection techniques C-scan is the most widely used in industrial manufacturing advanced composite materials. At this time, there are no standards that can be applied universally or procedures for inspection ultrasonic C-scan for advanced composite based materials which may cause the reliability and traceability of these methods has been limited. In response to this need, the study of methods and testing of advanced composite materials has been carried out. This assessment has produced three procedures 1. to operate the equipment C-scan through the pulse echo method, 2. producing the reference panel which reference panel is produced by a method recognized for its quality and usability of advanced composite panel produced aims to simulate defects. 3. Perform advanced analysis with use software such as Matlab®, which aims to analyze the defects in the form of three-dimensional images. This thesis gives an overview of the objectives and research activities to be carried out. As a finding, evaluation performance between destructive and image processing technique shown that comparable results between each other. Sample indicated O1 was determined as a best sample among others with lowest defect (i.e. porosity and void) percentage. It involved in no debulking process with normal vacuum bagging technique assisted by two (2) vacuum sources with polytetrafluoroethylene film on mould surface to enhance flow during fabrication. Supporting analysis should be carried out in order to analyze qualitatively.